Comparative effectiveness of cefazolin versus ceftriaxone or piperacillin/tazobactam for methicillin-susceptible Staphylococcus aureus bacteremia: a retrospective single-center study - Yusuke Takeuchi; Waki Imoto; Tomoyuki Yamada; Shigenobu Ishida; Kayoko Yamada; Masayo Kawamura; Hirokazu Minamimura; Tomoe Tago; Ikuko Hoshi; Yuichi Koizumi (Journal of Pharmaceutical Health Care and Sciences, 2026)
Abstract Background Cefazolin and antistaphylococcal penicillins are standard therapies for methicillin-susceptible Staphylococcus aureus (MSSA) bacteremia. However, few studies have evaluated the effectiveness of cefazolin monotherapy compared with alternative therapies for MSSA bacteremia. This study aimed to evaluate the effectiveness of cefazolin monotherapy in this clinical context. Methods We conducted a single-center, retrospective cohort study of adult patients with MSSA bacteremia treated between January 2010 and December 2022. Patients were categorized into a cefazolin group or a non-cefazolin group (receiving ceftriaxone or piperacillin/tazobactam) based on the therapy initiated within 48 hours of positive blood culture results. The primary endpoint was 90-day treatment failure. Univariable and multivariable Cox proportional hazards models were used to evaluate the primary endpoint. Results In total, 106 patients were included. The primary endpoint occurred in 22 (36.7%) and 26 (56.5%) patients in the cefazolin and non-cefazolin groups, respectively. Univariable analysis revealed that cefazolin therapy was significantly associated with a decreased risk of the primary endpoint compared with non-cefazolin therapy (hazard ratio [HR], 0.54; 95% confidence interval [CI], 0.30–0.95; p = 0.031). In multivariable analysis, cefazolin therapy remained significantly associated with a reduced risk of the primary endpoint (adjusted HR, 0.44; 95% CI, 0.24–0.82; p = 0.010). Conclusions Our findings indicate an association between cefazolin therapy and a lower risk of 90-day treatment failure compared with ceftriaxone or piperacillin/tazobactam for the treatment of MSSA bacteremia. Large-scale prospective studies are warranted to further evaluate the effectiveness of cefazolin monotherapy for this infection. Trial registration Not applicable.